Daylight intensity analysis of secondary school buildings for environmental development. (November 2019) - Irnawaty, I; Ramli Rahim, M.; Hamzah, Baharuddin; Jamala, Nurul
Abstract: Environmental development can be achieved by implementing energy efficiency in buildings. According to International Energy Agency (IEA) data, the lighting sector consumes 20% of world electricity production, contributes 6% of global CO2 emissions and as much as 3% of world oil demand for the same purpose. Natural lighting is the best lighting source for buildings, including school buildings. By optimizing the lighting in the building, it will save energy use in the building. This study discusses the compatibility of natural lighting in junior high school classrooms and meets SNI 03-6197-2000 standards for building lighting. The method of this research is quantitative, data obtained through survey measurements directly at the study site. There are four junior high schools in the city of Makassar that were used as research samples. The sample was chosen by purposive sampling. In each school, morning measurements are carried out until noon. The results showed that most of the natural light in junior high school classrooms in Makassar City was below the average lighting standards of SNI classrooms. A total of 75.00% of the SNI standard is average for classrooms and only 25.00% exceeds the SNI standard value.